2020
DOI: 10.1038/s41598-020-63493-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Changes of Temporomandibular Joint Osteoarthritis on Computed Tomography

Abstract: this study aimed to understand long-term changes of the osteoarthritic temporomandibular joint (tMJ) condyle using computed tomography (ct) and to verify its correlation with clinical characteristics of temporomandibular disorders. Eighty-nine patients (152 joints; 76 female, 13 male) who had taken follow-up CTs (mean follow-up period: 644.58 ± 325.71 days) at least once in addition to their initial evaluation were selected. cross-sectional demographic and clinical data and longitudinal ct images were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 61 publications
1
27
0
1
Order By: Relevance
“…6 TMJ-OA affects the cartilage, subchondral bone, synovial membrane, and other hard and soft tissues, causing changes such as condylar flattening, sclerosis, resorption, erosion, subcondylar cyst, or osteophyte formation. 7 Degenerative changes in the form of erosion, sclerosis, or resorption of the articular eminence are also characteristic of TMJ-OA. [8][9][10] The results of epidemiological studies of the prevalence of TMJ-OA vary due to the existence of different diagnostic criteria for the condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 TMJ-OA affects the cartilage, subchondral bone, synovial membrane, and other hard and soft tissues, causing changes such as condylar flattening, sclerosis, resorption, erosion, subcondylar cyst, or osteophyte formation. 7 Degenerative changes in the form of erosion, sclerosis, or resorption of the articular eminence are also characteristic of TMJ-OA. [8][9][10] The results of epidemiological studies of the prevalence of TMJ-OA vary due to the existence of different diagnostic criteria for the condition.…”
Section: Introductionmentioning
confidence: 99%
“…The most notable challenge in assessing the prevalence of TMJ-OA is the widely recognized disparity between objective diagnosis based on imaging evidence and subjective findings in the form of patient reports of pain or disability. 7,14,15 However, objective diagnoses (such as those made using imaging modalities) provide more reproducible results and facilitate more accurate comparative studies than subjective findings. 15 Although several studies have provided evidence regarding the prevalence of OA of the knee or other joints, very little is known about the prevalence of TMJ-OA.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have recently focused on inflammation and remodelling of subchondral bone during the early stage of TMJ OA, which may elucidate the possible mechanism of initiation and progression of the disease. 7,8 It has been suggested that catabolic processes overpower the anabolic capacity of chondrocytes with continued degeneration, tipping the homeostatic balance and resulting in progressive cartilage destruction. 9,10…”
Section: Osteoarthrosis Vs Osteoarthritismentioning
confidence: 99%
“…These results clearly presented the positive aspect of adjuvant sodium diclofenac administration to occlusal splint therapy on earlier pain reduction. Song et al [ 75 ] found that therapy with occlusal stabilization splints as well as administration of NSAIDs significantly improved TMJ OA. The pharmacotherapy with diclofenac sodium lasted 61.91 ± 42.15 days (the dosage was not presented).…”
Section: Nsaids In the Treatment Of Tmj Oamentioning
confidence: 99%
“…Table 2 presents the effectiveness of orally administered NSAIDs in the treatment of TMJ OA on the basis of the literature [ 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Nsaids In the Treatment Of Tmj Oamentioning
confidence: 99%